PERENCANAAN BIDANG PETERNAKAN DALAM PERSPEKTIF GOOD GOVERNANCE - Sujarwo, Mr. (FIA UB, 2012)
Development planning in regional autonomy era has given vast authority to built its region in accord with regional ability. Planning in animal husbandry as strategic sector to support national development planning should involved stakeholders from the government, private and community. These involvement within the frame of good governance would ensure planning based on available potential, appropriate planning process and knowing existing barriers, therefore eventually would produce plans in accord with regional needs. Ideas in study of this discipline has been giving description of good governance implementation in regional area.